2013 Pilot External Sector Report. (Policy Papers; Policy Paper ;, 2013)
The IMF's Second Pilot External Sector Report presents a multilaterally consistent assessment of the largest economies' external sector positions and policies for 2012-2013 H1. The report integrates the analysis from the Fund's bilateral and multilateral surveillance to provide a coherent assessment of exchange rates, current accounts, reserves, capital flows, and external balance sheets. The report takes into account feedback received on the previous report by placing a greater emphasis on capital flows and through further refinements to the EBA methodology. Together with the Spillover Report and Article IV consultations (with their heightened focus on spillovers), this Report is part of a continuous effort to ensure the Fund is in a good position to address the possible effects of spillovers from members' policies on global stability and monitor the stability of members' external sectors in a comprehensive manner.